2016
DOI: 10.48550/arxiv.1610.06303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weak Solution of a Doubly Degenerate Parabolic Equation

Di Kang,
Tharathep Sangsawang,
Jialun Zhang

Abstract: This paper studies a fourth-order, nonlinear, doubly-degenerate parabolic equation derived from the thin film equation in spherical geometry. A regularization method is used to study the equation and several useful estimates are obtained. The main result of this paper is a proof of the existence of a weak solution of the equation in a weighted Sobolev space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…In the present article, we obtain the existence of weak solutions in a wider weighted classes of functions than it was done in [11]. Moreover, we show the existence of non-negative strong solutions and we also prove that this solution decays asymptotically to the flat profile.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the present article, we obtain the existence of weak solutions in a wider weighted classes of functions than it was done in [11]. Moreover, we show the existence of non-negative strong solutions and we also prove that this solution decays asymptotically to the flat profile.…”
Section: Introductionsupporting
confidence: 56%
“…which describes the behavior of a thin viscous film on a flat surface under the effect of surface tension, the equation (1.1) is not yet well analysed. To the best of our knowledge, there is only one analytical result [11] where the authors proved existence of weak solutions in a weighted Sobolev space. In 1990, Bernis and Friedman [2] constructed non-negative weak solutions of the equation (1.3) when n 1, and it was also shown that for n 4, with a positive initial condition, there exists a unique positive classical solution.…”
Section: Introductionmentioning
confidence: 99%
“…After the change of variable x = − cos θ, the coupled system of evolution equations for h(θ, t) (14) and Γ (θ, t) (20) and their conservation properties (17) and ( 22) can be written more compactly as…”
Section: Model Formulationmentioning
confidence: 99%
“…The lubrication approximation is the classical approach for studying the dynamics of thin viscous films. In spherical geometry, which is the one we adopt in our work, well-posedness of the thin film model was analyzed in [30,20]. The motion of a Newtonian viscous fluid layer on a solid horizontal plane, with a monolayer of insoluble surfactant on its surface was modeled by Jensen and Grotberg [17] resulting in:…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1.2) is a particular case of (1.1) with a = b = 0 with an absence of the second-order diffusion term. Existence of weak solutions for (1.2) in a weighted Sobolev space was shown in [13] and existence of more regular non-negative strong solutions of (1.2) was recently proved in [16]. Unlike the classical thin film equation…”
Section: Introductionmentioning
confidence: 99%